Siri Marriage in Positive Legal Perspective - Syafruddin Syafruddin (Budapest International Research and Critics University, 2021)
This study aims to determine the policy the law against the act of unregistered marriage by the penghulu based on positive law in Langsa City, Then the factors that influence unregistered marriage and the impact of unregistered marriage according to positive law. That policyThe law against the act of unregistered marriage by the penghulu based on the Criminal Code that occurred in Langsa City violated the lawArticles 151 and 143 Draft Law on Material Law for Religious Courts (RUU HMPA)In 2007, it was judged that the act of unregistered marriage by the head of the village violated the criminal law and state administrative law, but so far in Langsa City there has been no confirmation of the crime against the perpetrators of the act of unregistered marriage. The factors that influence unregistered marriages in Langsa City are: factors of lack of awareness of the law, Religion factor, factor economy and status of children born considered an illegitimate child, so that in the eyes of the law he does not have a civil relationship with his father but only has a civil relationship with his mother and his mother's family (Articles 42 and 43 of Law No. 1 of 1974 and Article 100 KHI). The impact of unregistered marriage according to positive law due to not complying with the law in Pidie Regency, namely: the position of the wife is not recorded in the state administration, the position of children born from unregistered marriages is considered a child out of wedlock (considered illegitimate) by the State and joint property (Gono-Gini) in marriage if there is a divorce, the wife is difficult to get rights to joint property them if the husband does not give. In addition, if there is an inheritance left by the husband, because the husband dies, the wife and children are also very difficult to get the rights to the inheritance.DI hope the community does not carry out serial marriages, especially for women so that they do not become disastrous in the future. It is hoped that the Government will confirm criminal acts for perpetrators who carry out unregistered marriages, so that people do not carry out behavior that is detrimental to other parties.